Late Presentation of an Iatrogenic Pseudoaneurysm of the Profunda Femoris Artery following Intramedullary Nailing - Kira Vande Voorde; Jan Dauwe; Jan Van Oost (Case Reports in Orthopedics)
Introduction. Hip fractures are one of the most common osteoporotic fractures, and the incidence is expected to increase in the future. Vascular injury of the femoral vessels, although uncommon, is an intermittently reported complication in the treatment of proximal femoral fractures. This may be iatrogenic or less frequently as a result of the fracture itself. The profunda femoris artery is most commonly involved, probably because of its close relationship to the femur in the subtrochanteric region. Case Presentation. We report a well-documented case of pseudoaneurysm of the profunda femoris artery after intramedullary nailing of an intertrochanteric femoral fracture. Arterial damage was due to overpenetration when drilling the distal locking hole. Because of the late presentation, pressure on the medial femoral diaphysis caused severe cortical scalloping. This resulted in an obvious radiographic image rarely reported before. Conclusion. This case report illustrates the uncommon complication of pseudoaneurysm after intramedullary hip nailing. Because of the risk of potentially limb- and life-threatening complications, we advise careful drilling and placement of the distal locking screw. Excessive screw length should be avoided. The injured limb should be returned to the neutral position and lower-limb traction should be reduced before drilling the distal locking hole.